Strategy for Managing Solid Medical Waste at Health Care Facilities (Fasyankes) Within the Working Area of the Balai Jaya Community Health Center, Rokan Hilir Regency - Rikcart Padot Sianturi; Eni Sumiarsih; Dedi Afandi (CV. Publikasi Indonesia, 2026)
This research aims to analyze the existing conditions of solid medical waste management, identify internal and external factors influencing medical waste management, and formulate a solid medical waste management strategy in health care facilities (fasyankes) within the working area of the Balai Jaya Community Health Center (Puskesmas), Rokan Hilir Regency. The research employed a descriptive approach using SWOT analysis. Data were obtained through observations, in-depth interviews, and documentation studies conducted at various types of health care facilities within the working area of the Balai Jaya Community Health Center. The analysis was performed using the IFAS and EFAS matrices to determine the strategic position of solid medical waste management. The results indicate that solid medical waste management in the Balai Jaya Community Health Center’s working area is not yet optimal. The improper mixing of medical and nonmedical waste is still observed, waste containers do not fully comply with established standards, Temporary Storage Facilities (Tempat Penyimpanan Sementara [TPS]) for hazardous and toxic waste (Bahan Berbahaya dan Beracun [B3]) do not meet requirements in some health care facilities, dedicated waste management personnel are unavailable, and regular training on medical waste management has not been implemented. Furthermore, most health care facilities do not routinely weigh and record waste generation, resulting in inadequate documentation of waste management practices. Internal factor analysis indicates that the primary strengths include health care workers’ knowledge of medical and hazardous waste management, the use of personal protective equipment, and their awareness of occupational health and safety.